2022
DOI: 10.1007/s40618-022-01920-5
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic architecture between type 2 diabetes and COVID-19 severity

Abstract: Purpose Patients with type 2 diabetes (T2D) have demonstrated a higher risk for developing more severe cases of COVID-19, but the complex genetic mechanism between them is still unknown. The aim of the present study was to untangle this relationship using genetically based approaches. Methods By leveraging large-scale genome-wide association study (GWAS) summary statistics of T2D and COVID-19 severity, linkage disequilibrium score regression and Mendelian randomization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Furthermore, the analysis reveals an elevated risk of developing T2D in individuals with severe and hospitalized cases of COVID‐19. Nevertheless, some MR investigations have shown that there may not be a substantial correlation between T2D and the phenotype of COVID‐19 37,38 . In their review, Grubišić et al 39 proposed that COVID‐19 can potentially trigger the development of diabetes via the induction of immunological imbalance and glucose metabolism disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analysis reveals an elevated risk of developing T2D in individuals with severe and hospitalized cases of COVID‐19. Nevertheless, some MR investigations have shown that there may not be a substantial correlation between T2D and the phenotype of COVID‐19 37,38 . In their review, Grubišić et al 39 proposed that COVID‐19 can potentially trigger the development of diabetes via the induction of immunological imbalance and glucose metabolism disruption.…”
Section: Discussionmentioning
confidence: 99%
“…and the phenotype of COVID-19. 37,38 In their review, Grubišić et al 39 proposed that COVID-19 can potentially trigger the development of diabetes via the induction of immunological imbalance and glucose metabolism disruption. There exists a strong correlation between hyperglycemia and several factors, such as the duration of hospitalization, 40 the incidence of infection, 41 and the deterioration of patient outcomes 42 in individuals diagnosed with AP.…”
Section: Potential Confounding Factors and Mechanismsmentioning
confidence: 99%
“…COVID-19 is highly infectious, shows rapid mutation, and has become a global pandemic, resulting in high morbidity and mortality due to complications . Previous studies have shown a significant genetic correlation between T2DM and COVID-19 (Wu K. C. H. et al, 2022;Ni et al, 2023). Furthermore, Mendelian randomization has demonstrated a causal relationship between genetic susceptibility to T2DM and SARS-CoV-2 infection and hospitalization due to COVID-19 (Host Genetics Initiative, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…This is supported by extensive population-based genome-wide association studies (GWAS), which suggest that a number of common genetic variants can affect the severity of symptoms following a COVID-19 infection 4 , 19 . The genes most strongly associated with severe COVID-19 progression, as identified by GWAS, typically play roles in immune response mechanisms, lung disease pathology, CVD 20 , and T2D 21 .…”
Section: Introductionmentioning
confidence: 99%